A Baptismal Theology of Accountability - Torrance, Andrew (2021)
This article addresses the question of what it means to be accountable to God based on a baptismal theology that we find in the New Testament. It argues that various passages in the New Testament lead us to the view that we are accountable to God in Christ. Such a view is not straightforward, and so much of this article will be spent unpacking what this could mean. To do so, I elaborate on what it means for God to create humanity to find fulfilment in and through Christ. This leads me to argue that humans experience fulfilment in and through the body of Christ into which baptism initiates a person. It is by participating and finding belonging in the life of the Church that humans can begin to discover what it means to be accountable to God in Christ, and, in so doing, form the virtue of accountability.
Keywords: Virtue; Narrative; Jesus Christ; Holy Spirit; Church; Baptism; Apostle Paul; Accountability